1978
DOI: 10.1042/bj1760257
|View full text |Cite
|
Sign up to set email alerts
|

New reaction sequences for the non-oxidative pentose phosphate pathway

Abstract: 1. Reactions leading to the formation of 14C-labelled volatile compounds and compounds volatile under acid conditions were investigated in a system actively synthesizing hexose 6-phosphates from [U-14C]ribose 5-phosphate by reactions catalysed by enzymes prepared from acetone-dried powder of rat liver; no reactions involving 14C-labelled volatile compounds were detected. Similarly the fixation of 14C-labelled volatile compounds into hexose 6-phosphate could not be detected. 2. A complete carbon balance was mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 57 publications
3
28
0
Order By: Relevance
“…Its concentration in control liver perfusions was ~10 nmol/g tissue ( fig.2) which is similar to 5-7 nmol/g tissue found in [20]. This intermediate plays a r61e in the proposed L-type pentose pathway [35,36], and the existence of octulose phosphates [19,20] support the operation of this pathway. However, there does appear to be some doubt regarding the metabolic fate of arabinose 5-P another key intermediate in the L-type pentose pathway [33,34].…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Its concentration in control liver perfusions was ~10 nmol/g tissue ( fig.2) which is similar to 5-7 nmol/g tissue found in [20]. This intermediate plays a r61e in the proposed L-type pentose pathway [35,36], and the existence of octulose phosphates [19,20] support the operation of this pathway. However, there does appear to be some doubt regarding the metabolic fate of arabinose 5-P another key intermediate in the L-type pentose pathway [33,34].…”
Section: Resultssupporting
confidence: 67%
“…In the glucagon treated liver, the increased altro heptulose 7-P concentration would be due to the same set of reactions as above, together with a decreased utilization ofaltro heptulose 7-P by phosAlthough there appears to be some debate regarding the mechanism of the non-oxidative pentose phosphate pathway in liver [31][32][33][34], there is very clear evidence for the existence in liver tissue of altro heptulose 1,7-P2 (here and [19,20]). Its concentration in control liver perfusions was ~10 nmol/g tissue ( fig.2) which is similar to 5-7 nmol/g tissue found in [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4) [183]. Based mainly on carbon balance studies and on experiments involving tracing of 14 C labelled sugars, Williams and coworkers have proposed an alternative version of the PPP, the so called`L -type'', which apparently operates in hepatocytes from rats [178]. In this type of the PPP glucose 6-phosphate also acts as an acceptor substrate for TK, resulting in the generation of an octulose [66,179,180].…”
Section: Substrate Speci®citymentioning
confidence: 99%
“…Thus, with unlabeled ribulose 5-P being formed in the oxidative portion from unlabeled glucose, here from the glucose load, and [1-14C]ribose, isotopic nonequilibration of the pentose 5-phosphates, resulting in higher specific activities of ribose 5-P than of xylulose 5-P, explains the incorporations into carbon 3 related to those in carbon 1 (17). Williams et al (21) reported that 14C was incorporated into carbon 2 ofglucose 6-P when (1-14C]ribose 5-P was incubated for short periods with a rat liver enzyme preparation. Reactions yielding such incorporation, with the oxidative portion ofthe pentose pathway, comprise the L-type pathway that he and his coworkers proposed ( Fig.…”
Section: Resultsmentioning
confidence: 99%